2018
DOI: 10.1080/15384047.2018.1480290
|View full text |Cite
|
Sign up to set email alerts
|

Double amplifications of CDK4 and MDM2 in a gastric inflammatory myofibroblastic tumor mimicking cancer with local invasion of the spleen and diaphragm

Abstract: Inflammatory myofibroblastic tumor (IMT) is currently recognized as an intermediate mesenchymal neoplasm. It can arise anywhere in the body, but it is particularly common in the lungs. Gastric IMT is very rare in adults. In this study, we report a case of a 68-year-old woman with IMT in the gastric cardia, with invasion into the spleen and diaphragm. Because of its location and aggressive clinical features, it was first mistaken for gastric cancer. However, pathology and immunohistochemistry were used to final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The amplifications in the mentioned regions might promote clinical features related to metastatic homing and tumor invasion that mimic WT. The co-amplification of CDK4/MDM2 has also been noted to change the location and clinical features of rare cases of inflammatory myofibroblastic tumors, causing them to be mistaken for gastric cancer with local invasion of the spleen and diaphragm 55 . Predilection for lung metastasis have been confirmed in several malignancies such as melanoma, sarcoma, kidney- and breast cancer, in which the preferential site for metastasizing also is subtype dependent 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The amplifications in the mentioned regions might promote clinical features related to metastatic homing and tumor invasion that mimic WT. The co-amplification of CDK4/MDM2 has also been noted to change the location and clinical features of rare cases of inflammatory myofibroblastic tumors, causing them to be mistaken for gastric cancer with local invasion of the spleen and diaphragm 55 . Predilection for lung metastasis have been confirmed in several malignancies such as melanoma, sarcoma, kidney- and breast cancer, in which the preferential site for metastasizing also is subtype dependent 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Although mouse double minute 2 ( MDM2 ) gene amplification has also been detected in 27% of IMT cases, no data are available at this moment regarding the efficacy of MDM2 inhibitors alone or in combination with CDK4 inhibition [ 49 , 50 ].…”
Section: Current Treatmentsmentioning
confidence: 99%
“…They all bene ted from treatment with crizotinib (250 mg) with a signi cant reduction in tumor size. (31)(32)(33)(34) Jia He et al found for the rst time a double ampli cation of CDK4 and MDM2 with protein overexpression by NGS and IHC in a 68-year-old woman with a gastric IMT with local invasion of spleen and diaphragm (35). Furthermore, Antonescu et al found correlations between the genotypes and certain clinic-pathologic characteristics of the IMT .…”
Section: Discussionmentioning
confidence: 99%